Self-Compassion dan Negative Emotional States Pada Mahasiswa Kedokteran Umum: Hubungan dan Prevalensi - Anindhita Parasdyapawitra Amaranggani; Thalia Tresnaning Prana; Ni Made Cintya Dwiyanti Arsari; Agung Maulana Surbakti; Amalia Rahmandani (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2021)
Negative emotional states, such as depression, anxiety, and stress, can arise and impact the individual's adaptive function. Self-compassion includes treating oneself with wisdom and understanding when faced with suffering, which helps improve self-regulation in dealing with emotional problems. This study aims to see the relationship between self-compassion and negative emotional states in Diponegoro University medical students, involving 118 participants of second-year students using the convenience sampling technique. Measurements in the study were carried out using the self-compassion scale (22 items, α = 0.925) and the DASS-21 Indonesian version (21 items, α = 0.892). Spearman's rho showed a significant negative relationship between self-compassion and negative emotional states (rxy = -0.630, p = 0.000). Self-compassion was also found to have a significant negative relationship with depression (rxy = -0.643, p = 0.000), anxiety (rxy = -0.440, p = 0.000), and stress (rxy = -0.516, p = 0.000). These results indicate that the higher self-compassion of the participants, the lower the negative emotional states, and vice versa. Self-compassion predicts negative emotional states in participants ranging from depression, stress, and anxiety sequentially. The further identified prevalence of negative emotional states in participants in this study. A program to enhance self-compassion is needed to reduce negative emotional states.